El desarrollo emocional para fortalecer el lenguaje oral en los niños de 2 a 3 años, del centro infantil del buen vivir “Villa María”, del Cantón Riobamba, Provincia Chimborazo, Parroquia Maldonado, en el año lectivo 2014-2015. - Moreno Chica, Nataly Eugenia (2016)
This research focuses on having a new vision on education. It uses emotional growth in order to strengthen oral communication. Firstly, the research subject, and both general and specific objectives were proposed. The problem was then formulase and justified; it details the theoretical framework which contains the scientific and theoretical foundations were presented. It contains topics and subtopics that discuss the two study variables which were investigated by several authors with different points of view. Basic terms, assumption, hypothesis and functionality of variables were defined. Inductive, deductive, descriptive, bibliographical and field methods were used. Tools and techniques like observation and an observation sheets were handled on the children. The topic will permit comprehension, and identify and control emotions. They will later assist in the development of empathy, which will promote self-esteem, confidence, safety and motivation. This will strengthen oral language which will allow the children to develop their verbal capacity, expand vocabulary and phrases so that they can communicate clearly to an adult. Our proposal was to create a teaching guide called “Aprendiendo Mis Emociones” to be used by teachers. These activities will be useful in the teaching and learning process which is expected to improve oral language in children through exercises: apraxia, poems, songs, rhymes, onomatopoeia sound and to know and identify their emotion. This will allow the child to have emotional progress according to their age and optimum wellbeing.